Oral Health Disparities in Type 2 Diabetes: Examining the Elevated Risk for Dental Caries—A Comparative Study - José Frias-Bulhosa; Maria Conceição Manso; Carla Lopes Mota; Paulo Melo (Dentistry Journal, 2025)
Background/Objectives: Dental caries (DCs) and type 2 diabetes share common risk factors. Dental caries risk in type 2 diabetics (T2DM) shows contradictory results. The aim of this study was to determine if there is a difference in DC prevalence in adults with and without T2DM and whether body mass index (BMI) classes or glycated hemoglobin (HbA1c) levels interfere in that difference. Methods: A total of 666 adults (n(T2DM) = 343; n(nT2DM) = 323), from Espinho Primary Health Care Center, were interviewed by calibrated observers. Data from clinical records were collected and oral health status was registered using WHO criteria. Inference analysis was conducted using non-parametric tests (α = 0.05). Results: A similar caries prevalence was found between the T2DM (98.2%) and nT2DM (98.8%) groups, with the T2DM group showing significantly higher tooth loss (p < 0.001), higher caries experience rerted as mean ± sd (17.7 ± 8.3 vs. 15.9 ± 7.8, p = 0.005), fewer decayed teeth (p < 0.001) and filled teeth (p = 0.016) compared to nT2DM. The most frequently identified comorbidity was hypertension (53.6%). Tobacco use (12.9%) was lower in T2DM (p < 0.001). The restorative and treatment indices indicated a significantly higher proportion of use of oral care services (p < 0.001) in T2DM individuals. The prevalence of the higher classes of BMI indicative of pre-obesity or obesity shows significant differences (p < 0.001). The differences found in the DMFT or each of its components for the prevalence or for the mean in HbA1c control were not statistically significant (p = 0.368, and 0.524, respectively). Conclusions: Adults with T2DM and higher BMI classes could be associated with a greater prevalence of DCs. The glycemic control of T2DM does not significantly influence DMFT score or each of its components.